Green Infrastructure Vulnerability and Regional Poverty Reduction: New Sustainable Development Recommendations Based on a Spatial Clustering Approach. - Sumargo, Bagus; Kurniawan, Robert; Nasution, Bahrul Ilmi; Firmansyah, Aldi; Laksono, Bagaskoro Cahyo; Gio, Prana Ugiana; Isnaeni, Mohamad Andrian; Yusuf, Mukhtar; Tarigan, Vita Cita Emia (Journal of Poverty)
Poverty is always associated with poor green infrastructure. Indonesia has a significant poverty rate and low green infrastructure investment. Therefore, this study uses fuzzy clustering with area weighting (FGWC-HHOP) and 2018 Potential Village Census (PODES) data to analyze green infrastructure risk and poverty in Indonesia. The first cluster, which is mainly urban, is vulnerable, while the second cluster has poor air quality and green infrastructure. Future government policies should encourage sustainable development, especially green infrastructure, to reduce social vulnerability. Consider green infrastructure and social vulnerability when planning urban expansion and poverty alleviation in Indonesia.